Penerapan Model Pembelajaran Kooperatif dalam Meningkatkan Karakter Percaya Diri - Mardina Wati; Sakban Sakban; Wismanto Wismanto (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Cooperative learning model is one of the models that can be used as an alternative. The use of small groups in cooperative learning makes students work together to achieve the learning objectives. The problems in this study are (1) How is the application of cooperative learning models in improving the character of self-confidence in civics subjects in class III SD Negeri 15 Pekanbaru (2) Whether the cooperative learning model can improve the character of self confidence in the subject of civics in class III. This research includes Classroom Action Research (PTK) which was conducted in two cycles using quantitative analysis and qualitative analysis methods. Each cycle consists of four stages, namely design, implementation, observation, and reflection. The subjects of this research were third grade students of SD Negeri 15 Pekanbaru, totalling 31 students. The research data were obtained using teacher and student observation sheets and student confidence test results, then the data were analysed using the percentage formula.The results obtained were (1) teacher activity in cycle I by using cooperative model from 72.11% to 92.15% in cycle II, (2) student activity in cycle I by using cooperative model from 45.71% to 83.69% and, (3) student learning outcomes in Civics subject in cycle I by using cooperative 32.25% to 83.87% in cycle II.This shows that the results of students' self-confidence in Civics subjects by using cooperative models show very positive results. Based on the results of this study, it can increase students' confidence to be more active and the teacher's ability to improve to be better.